Viajando pela educação da primeiríssima infância: sentidos, crenças e valores que sustentam os saberes e as práticas pedagógicas na/da creche - Rodrigues, Silvia Adriana [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This paper was developed linked to the line of research "Childhood and Education", and aims to present the results of research that had as study object the educational nursery environment - understood as a learning space (adults and children) to share and product a new knowledge and to live in the early childhood. According with the basic assumptions that in collective educational spaces, into the adult-child interactions, the role of the more experienced partner (in this case the teacher) is guided by the views and perceptions of the cultural group to which it belongs, which, in turn, direct the look on the child, its particular ways to understand and give meaning to its surroundings (physical and social), I defined as the central theme of this discussion the understanding that the meanings, values and beliefs that drive the pedagogical actions/practices of professionals who working in this space need to be “unveiled”. So I had delimited as the main objectives of this research to learn how the nursery institution has been performed its role to be a space for the promotion of human development, seeking to understand how professionals understand their own social role and the nursery’s role, adopting the principle that these both are configured as a privileged way of view, not as the entire nursery phenomenon, according its breadth, but one of the nodal points of its dynamic operation, based on the personal perception that it’s a responsibility of the professionals to “set the tone” or “stay the course” in the daily work of collective education institutions. There are also specific objectives: to understand how early childhood professionals realize the nursery environment, how they see and value this space and its social function; searching the ways of understanding the professional nursery (at training and at different times of action) on training, the knowledge and necessary actions for educational practice with little children; to discuss about interference (positive and negative) of understandings and beliefs (and hence actions) of professionals in the process of human development and children’s learning. Therefore, the research, inserted within the qualitative field of educational research, with exploratory character, had five subjects participants with different profiles, with the procedure for data collection using what I have called ‘the practice reports’, a hybrid instrument which brings elements of the interview and narrative in its constitution. The data analysis, performed using as its basic method the discourse analysis of Bakhtin’s ideology and his active responsive reading proposal, allowed me to ratify the understanding that the nursery is presented as polysemic and polyphonic space; there are multiple representations, perceptions, ideas, beliefs, values, thoughts, speeches and consequently practices, which make up what has materialized as an educational institution of the early childhood that, largely, lacks ruptures and changes in different aspects such as interpersonal relationships (between adults and children) more qualified; daily pedagogical organization grounded in play interactions and children's interests; effective articulation between the inseparable practices of care and educate, the value of training in specific courses, but also the daily built knowledge, among others. It was also possible to understand that teaching in this level of education (but not only in it) is built in a tangle of mixed possibilities that occurs along its trajectory (personal and professional), occurring in many ways. There are many remnants of interpretations ruled in ancient conceptions (but also very recent) about the child, childhood, kindergarten and teacher's role that must be overcome, giving way to an education understanding for younger children in collective spaces with social functions and specific educational, and, mainly, as a children right to be respected and promoted more effectively, a challenge presented to the training courses, but also for all segments involved in the causes of the early childhood education.

Vinculado à linha de pesquisa “Infância e Educação”, o presente trabalho apresenta os resultados da investigação que teve como objeto de estudo o ambiente educativo da creche – tomado como espaço de aprendizagens (de adultos e crianças), de compartilhamento e produção de novos conhecimentos e como um lugar de se viver à pequena infância. Tendo como premissas básicas que em espaços educacionais coletivos, nas interações adulto-criança, o papel do parceiro mais experiente (neste caso, o professor) é norteado pelas concepções e percepções do grupo cultural ao qual pertence, que por sua vez direcionam o olhar sobre a criança, suas formas peculiares de compreender e dar significados ao seu entorno (físico e social), defini como eixo articulador da discussão o entendimento de que os sentidos, valores e crenças que movem as ações/práticas pedagógicas dos profissionais que atuam neste espaço precisam ser “descortinados”. Assim, delimitei como objetivos centrais de investigação apreender como a instituição creche vem desempenhando seu papel de ser espaço de promoção do desenvolvimento humano, buscando entender como os profissionais compreendem o seu papel social e o da creche, adotando como princípio que esta se configura como uma forma privilegiada de perceber, não a totalidade do fenômeno creche, tendo em vista sua amplitude, mas, um dos pontos nodais de sua dinâmica de funcionamento, partindo da percepção pessoal de que cabe aos profissionais “dar o tom” ou “manter o rumo” do trabalho cotidiano das instituições coletivas de educação. Têm-se ainda como objetivos específicos: compreender como os profissionais da educação infantil percebem o ambiente da creche, como vêem e valoram este espaço e sua função social; esquadrinhar as formas de entendimento dos profissionais da creche (em formação e em diferentes momentos da atuação) sobre formação, saberes e ações necessários à pratica educativa com crianças pequeninas; discutir as interferências (positivas e negativas) dos entendimentos e crenças (e, consequentemente das ações) dos profissionais no processo de formação humana e aprendizagens das crianças. Para tanto, a investigação, inserida no campo qualitativo da pesquisa em educação, com caráter exploratório, teve como participantes cinco sujeitos, com perfis distintos, e como procedimento para coleta dos dados o uso do que denominei ‘relatos da prática’, um instrumento híbrido que traz elementos da entrevista e da narrativa em sua constituição. A análise dos dados, realizada usando como método básico a análise do discurso da vertente bakhtiniana e sua proposta de leitura responsiva ativa, permitiu ratificar o entendimento de que a creche se apresenta como espaço polissêmico e polifônico; são múltiplas as representações, percepções, concepções, crenças, valores, ideias, reflexões, discursos, e consequentemente práticas, que compõem o que se tem materializado como instituição educativa da primeiríssima infância que, em grande medida, carece de rupturas e transformações em diferentes aspectos, tais como relações interpessoais (entre adultos e crianças) mais qualificadas; organização pedagógica cotidiana calcada em interações lúdicas e nos interesses infantis; articulação efetiva das práticas de cuidar e educar de forma indissociada, no valor dado a formação em cursos específicos, mas também dos saberes construídos cotidianamente, entre outros. Foi possível ainda entender que a docência neste nível de ensino (mas não só nele) se edifica num emaranhado de possibilidades mescladas que se dão ao longo de sua trajetória (pessoal e profissional) e que ocorrem por muitas vias. Há muitos resquícios de interpretações pautadas em antigas (mas, muito presentes) concepções de criança, de infância e de creche, do papel do professor que precisam ser superados, dando lugar à compreensão de educação para as crianças bem pequenas em espaços coletivos com funções sociais e educacionais específicas, e principalmente, como um direito das crianças que precisa ser respeitado e mais eficazmente fomentado; um desafio que se apresenta aos cursos de formação, mas também para todos os segmentos envolvidos com as causas da educação da primeiríssima infância.
Traveling in the early childhood education: meanings, beliefs and values that underpin the knowledge and nursery educational practices
Keywords: Nursery educational practices; Early childhood education; Professional nursery; Práticas educativas na/da creche; Educação da primeiríssima infância; Profissionais da creche